#### Answer

$s' =3t^{\frac{1}{2}}$

#### Work Step by Step

$s = 2t^{\frac{3}{2}} + 3e^{2}$
$s' =2( \frac{3}{2})t^{\frac{1}{2}} + 0$
$s' =3t^{\frac{1}{2}}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$s' =3t^{\frac{1}{2}}$

$s = 2t^{\frac{3}{2}} + 3e^{2}$
$s' =2( \frac{3}{2})t^{\frac{1}{2}} + 0$
$s' =3t^{\frac{1}{2}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.